THE USE OF GEOMETRIC SHAPES IN THE CREATIVE DEVELOPMENT OF PRESCHOOL CHILDREN - Pulatov Foziljon Usibjonovich (Journals Park Publishing, 2024)
This article shows methods for developing the creative abilities of preschoolers using geometric shapes in educational drawing activities at the “Art” development center.
Keywords: Art, art activity, picture, oval, circle, square, triangle, rectangle, creativity, ability, image.